Enhancing National Development by Advancing Technical and Vocational Education in Nigeria to Foster Human Capital Development - Aliyu, Ibrahim Ladan (International Journal of Education, Culture, and Society, 2023)
The development of human capital in every nation holds great importance as it is closely intertwined with the nation's economic progress. Thus, it is crucial for each nation to explore avenues for advancing its economy. This research study aims to address the enhancement of Nigeria's human capital by focusing on the improvement of Technical and Vocational Education (TVET) to enhance its status and quality. TVET has been identified as a key contributor to the nation's human capital development. The study begins by providing an overview of Nigeria's human capital situation and proceeds to examine the role that TVET can play in fostering human capital development and addressing prevalent national challenges. Additionally, the study explores the advantages that human capital development can bring to the nation and delves into the contributions of TVET towards achieving this development. Finally, the research concludes by identifying the challenges associated with human capital development and proposing strategies for enhancing TVET in Nigeria, ultimately providing recommendations to address these challenges and problems.